Production and evaluation of biodegradable plastic films and their resistance to organic solvents - P Bassey; O Salokun; O.N. Aghedo; I.S. Hassan (Journal of Applied Sciences and Environmental Management, 2020)
The character of gelatinized cassava starch was studied with a view to deciphering its rate of organic solvent absorption. Solution casting method was employed in fabricating the cast films. Cassava starch (CS) was initially modified to produce thermoplastic starch (TPS) and Polyvinyl alcohol (PVA) added to the matix. Absorption test was also carried out by introducing glycerol into the mixture to completely gelatinize the blend. Each blended sample was dried in a closed vessel for 12 hours and then cured in the oven for half an hour at 800C. Finally, the film was peeled off from the glass plate and sealed for experimental use. Results revealed that increase in polyvinyl alcohol content produced a corresponding increase in organic solvent uptake rate. However, this results implies that the cast films could absorb more water (hydrophilic) and microorganisms in a soil water environment increasingly over time with an increasing starch content, thus leading to a greater biodegradation.